Comparison between perfusion and balloon techniques for performing anorectal manometry in children with intestinal constipation - Marques,Geraldo Magela Nogueira (2008)
INTRODUCTION: Two anorectal manometry techniques have commonly been utilized: the perfusion technique and the balloon technique. PURPOSE: To compare both techniques in children with intestinal constipation who had not undergone surgical treatment for its correction. METHODS: Thirty-nine children aged between four and fourteen years underwent anorectal manometry using both techniques at random. Resting pressure, pressure response to voluntary contraction, coughing and perianal stimulation, maximum pressure on the anal canal pressure curve, and presence of rectosphincteric reflex were registered and submitted to statistics. Vectorgraphy of the sphincter muscle complex was obtained by perfusion technique. RESULTS: The statistical comparison between the techniques revealed statistically significant differences in resting pressure (p=0.041), pressure response to voluntary contraction (p=0.026) and maximum pressure within the pressure curve (p=0.010). The rectosphincteric reflex was demonstrated in 21 patients by both techniques. CONCLUSIONS: The perfusion technique presented greater sensitivity in the following parameters: resting pressure, pressure response to voluntary contraction and maximum pressure within the pressure curve. The methods studied are equivalent regarding the measurement of pressure responses to coughing and perianal stimulation and the investigation of rectosphincteric reflex.